Integrating educational and health technologies for cattle farmers in the development of a renewable energy-based village in Kuripan, Demak - Buchori, Achmad; Prasetyowati, Dina; Kusumantoro, Adhi; Widodo, Suwarno; Pertiwi, Siti Maisyaroh Bakti (Community Empowerment, 2024)
Kuripan Village, Demak, possesses abundant cattle manure resources but faces challenges related to waste management and energy needs. This community engagement initiative aims to integrate educational and health technologies for cattle farmers to develop Kuripan Village into a renewable energy-based village. The methods employed included program socialization, training in virtual reality (VR)-based educational media creation regarding cattle manure utilization, health risk education on livestock waste and cattle farming business prospects, dissemination of information on biogas-based electricity generation systems, and the initiation of biogas reactor construction. The results indicate an increased understanding and skills among youth partners in VR educational media production, enhanced awareness among cattle farmers regarding health risks and the economic potential of cattle manure, comprehension of biogas-based electricity generation systems, and active community participation in the biogas reactor construction, which has reached a 60% completion stage. This program is expected to serve as a model for technology integration and community empowerment in realizing renewable energy-based villages.